Sex Worker Homicide Series: Profiling the Crime Scene - Sorochinski, Marina (International journal of offender therapy and comparative criminology, 2019)
Contrary to popular misconceptions, offenders who kill sex workers as part of their series exhibit substantial variability in their victim selection and behavioral patterns, thus creating additional issues for the investigation of these crimes. This article first aims to outline differences in the demographics of crime scene actions present in homicide series with exclusively sex worker victims and series that includes both sex worker and non-sex worker victims, with the aim of understanding the crime scene aetiology of these two different types of series. Second, the research aims to determine between-series differences of victimology as well as crime scene action between sex worker series and mixed-victim series. Third, the research focuses on mixed-victim series and aims to determine the within-series similarities of victimology and crime scene actions, that is, what factors link sex worker victims and non-sex worker victims in the same series. Data were collected through a large-scale review of international media sources to identify solved serial homicide cases that have included at least one sex worker. Of the 83 series looked at, 44 (53%) included sex worker victims only, and 39 (47%) of the series included both sex worker and non-sex worker victims. The findings highlight the challenges that these types of crime present for investigation and the implications they have on current crime analysis research and practice, and results are discussed in line with theoretical and psychological issues relating to understanding differentiation and similarity, as well as investigative implications relating to linkage blindness and linking of serial crimes.